The experience of removal of giant lipomas in an ambulatory surgery centre - D. M. Usoltsev; A. A. Davidyan; R. A. Babich (Амбулаторная хирургия, 2016)
The article analyzes the effectiveness of use of exogenous nitric oxide in outpatient settings for the treatment of traumatic purulent soft tissue infection complicated by inflammation and trophic lesions against a background of lower extremity varicose veins and diabetic foot syndrome.